Marketing by live streaming: How to interact with consumers to increase their purchase intentions - Liu, Feng; Wang, Yan; Dong, Xiaoxu; Zhao, Huawei (Frontiers in Psychology, 2022)
Live streaming e-commerce, as a kind of new information technology-based business model, is currently the most popular approach to marketing, especially in China. This research divides live streaming interactions into three dimensions: interactions for obtaining product information (IPI), interactions for grasping the purchase dynamics of others (IPD), and interactions for obtaining monetary incentives (IMI), and proposes a comprehensive framework to examine whether live streaming interactions with consumers promote both social presence and consumer conformity, thereby enhancing their purchase intentions. Covariance-based structural equation modeling (CB-SEM) with AMOS was conducted to analyze data collected from 576 Chinese consumers. The main findings are that, first, both IPI and IPD can exert a direct impact on social presence and consumer conformity; second, IMI only has a positive impact on social presence; and third, interactions tend to increase purchase intention through the social presence and consumer conformity. Furthermore, given the differences between experience and search products, the results of the multi-group analysis indicate inconsistent path coefficients between the two product groups. This research provides a new perspective for studying live streaming e-commerce and enriches the content of live streaming e-commerce literature and explores the practical implications for marketing managers are looking for marketing by live streaming.